Left heart remodeling as a risk factor for atrial fibrillation in patients after surgery of acquired heart defects - I. I. Averina; M. Yu. Mironenko; L. A. Glushko; S. A. Donakanyan; L. A. Bokeria (Российский кардиологический журнал)
Aim. To identify risk factors for atrial fibrillation (AF) in patients with aortic and mitral defects after surgical treatment.Material and methods. A total of 112 patients with aortic and mitral defects (excluding patients with mitral stenosis) were examined: 90 men and 22 women aged 18 to 72 years (median age, 51(35;57) years). Patients were examined initially before and after surgery (in terms of 8-14 days and after 12-36 months). The peak left atrial (LA) longitudinal strain (PALS) was determined at LA reservoir phase. The following endpoints were chosen: the presence of AF and atrial flutter (AFL) in the shortand long-term period after surgery, repeated hospitalization for arrhythmias. Patients were divided into 2 groups: group 1 — patients with a favorable prognosis, group 2 — patients with AF and AFL after surgery. The mean values were compared by the independent Student’s t test, while the rank sum — by the Mann-Whitney test. ROC analysis was used.Results. Baseline LA volume index (LAVI) >44,4 ml/m2 increased the risk of AF after surgery (AUC=0,6±0,07, p<0,05, relative risk (RR) — 2,34 (confidence interval (CI), 0,8-6,88). LA volumes were within the normal range in the group without arrhythmias. A decrease in the initial threshold level of LA PALS <27,5% increased the risk of AF as in the shortand long-term postoperative period (AUC=0,659±0,08, p<0,01, RR — 1,19 (CI, 3,38-31,4). In the AF group, PALS decreased after surgery and did not increase in the long-term period (28±7,5% at baseline, 19±6,2% after surgery, 21±8,3% in the long-term period, (p=0,04 and p=0, 23, respectively). Left ventricular ejection fraction affected the AF development only in the early period after surgery (AUC=0,71±0,049, p<0,008, RR — 2,21 (CI, 1,27-3,87).Conclusion. The development of AF was influenced by LAVI, LA PALS, while in the early postoperative surgery period — ejection fraction.